Studies within a trial priorities to improve the evidence to inform recruitment and retention practice in clinical trials. Issue 4 (September 2022) - Boxall, Cherish; Treweek, Shaun; Gillies, Katie; ,
Background: Trial execution commonly relies on experience and judgement because there is a lack of evidence to inform how best to design and deliver clinical trials. Recruitment and retention are critical determinants to trial success have been persistent challenges that impact various stakeholders including funders, researchers, and the public. Studies within a trial (SWATs) are a way to discover best practices for recruitment and retention strategies, however, the current SWAT landscape has not been formally explored to date. This study aimed to (i) identify where current activity is taking place (ii) understand if SWATs are addressing PRioRiTY questions (iii) highlight gaps in the literature for future research. Methods: In November 2020, registered SWATs in the SWAT repository store were extracted and categorised into 'recruitment', 'retention' or 'other' based on the primary outcome. Recruitment and retention SWATs were subsequently mapped against PRioRiTY 1 and 2 questions and descriptive statistics were used to present the findings. Results: 125 registered SWATs were extracted from the repository. 50 and 36 SWATs reported recruitment and retention as their primary outcome, respectively. A majority of recruitment SWATs investigated what and how information should be designed and delivered to potential trial participants ( n = 23, 46%) and the advantages and disadvantages of using technology during the recruitment process ( n = 9, 18%). Three of the Top 10 PRioRiTY 1 questions had no SWATs mapped against them. A majority of retention SWATs focused on the best ways to encourage participants to complete trial tasks ( n = 24, 67%), how incentives should be implemented ( n = 10, 28%) and strategies to make participants feel valued ( n = 9, 25%). Five of the Top 10 PRioRiTY 2 questions had no SWATs mapped against them. Conclusions: This study identified a mismatch between registered SWAT activity and the priority questions in recruitment and retention. Trial teams should consider the PRioRiTy 1 and 2 questions for recruitment and retention, respectively, when designing a SWAT. In addition, there is a great breadth of research taking place, but replication of existing research is needed to produce confident evidence-based guidance for trialists and researchers to implement into their work.